Bank danych regionalnych GUS jako podstawa analiz ilościowych w oprogramowaniu GRETL i R - Błażejowski, Marcin; Kufel, Paweł; Kufel, Tadeusz (Central Statistical Office's Regional Data Bank as a Basis for Quantitative Analysis in GRETL and R, 2009)
The purpose of this article is to present Regional Data Bank of Central Statistical Office for GRETL (GNU Regression, Econometric and Time-series Library). Built databases concern over 1500 cross-sectional series for the years 1999-2006 in district and voivodeship structure. Some quantitative analyses for this database are presented, from spatial econometrics area as well as clustering and classification, which were computed using functions of R package integrated in GRETL package. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 97-103